Environmental and hygienic assessment of territorial burden and composition range of pesticides utilized in agriculture of northern region of Kazakhstan (Eurasian Journal of Ecology, 2016)
There was analyzed the intensity of pesticide use in the northern region of Kazakhstan by the indicator of territorial pesticide burden and integral index of territorial burden. Despite the average level of territorial burden in the assessed region, the analysis by the Oblasts has revealed that in certain Rayons of the Oblasts this indicator was over 1 kg/hectare. The highest specific weight in the structure of pesticide burden belongs to the active substances of the 3rd class of hazard, with low probability of carcinogenic effect, moderately stable in the soil.
Keywords: pesticides; territorial pesticide burden